Composition and functionality of bacterioplankton communities in marine coastal zones adjacent to finfish aquaculture. (September 2022) - Da Silva, R.R.P.; White, C.A.; Bowman, J.P.; Ross, D.J.
Abstract: Finfish aquaculture is a fast-growing primary industry and is increasingly common in coastal ecosystems. Bacterioplankton is ubiquitous in marine environment and respond rapidly to environmental changes. Changes in bacterioplankton community are not well understood in semi-enclosed stratified embayments. This study aims to examine aquaculture effects in the composition and functional profiles of the bacterioplankton community using amplicon sequencing along a distance gradient from two finfish leases in a marine embayment. Results revealed natural stratification in bacterioplankton associated to NOx, conductivity, salinity, temperature and PO4 . Among the differentially abundant bacteria in leases, we found members associated with nutrient enrichment and aquaculture activities. Abundant predicted functions near leases were assigned to organic matter degradation, fermentation, and antibiotic resistance. This study provides a first effort to describe changes in the bacterioplankton community composition and function due to finfish aquaculture in a semi-enclosed and highly stratified embayment with a significant freshwater input. Graphical abstract: Unlabelled Image Highlights: Aquaculture abundant taxa were related to biochemical processes, pathogens, and fish gut microbiome Aquaculture enriched functional profile were related to organic matter degradation, fermentation, and antibiotic resistance Differences between leases could be related to changes in hydrodynamics, location, and production and management practices